Employee Performance Driven by Innovation and Knowledge Sharing - Gunawan, Asep; Febriyansyah, Hevy; Fitri, Mutiara Eka (Al-Qalam Institue, 2025)
This study investigates the influence of individual innovation capability and knowledge sharing on employee performance. Using a quantitative correlational approach, data were collected through questionnaires distributed to 67 employees across six beauty salons. The results of multiple linear regression analysis revealed that both individual innovation capability (β = 1.124, sig. = 0.000) and knowledge sharing (β = 1.275, sig. = 0.000) have a significant and positive effect on employee performance. These findings suggest that employees who are open to new ideas, creative in solving problems, and willing to exchange knowledge with their peers tend to perform better in service-based tasks. The study emphasizes the importance of fostering a work environment that promotes innovation and collaboration to support sustained employee performance. It also highlights the need for future research to consider additional variables such as organizational support or leadership style to better understand performance drivers in similar contexts.